Enhancing Student Interest in English Learning Through Interactive Learning Media - Fatimah, Nur; Seriwati, Sunar (Indonesian Journal of Pedagogical and Social Sciences, 2024)
Abstract. The research aimed to enhance students' interest in learning English by utilizing various interactive learning media. The researcher conducted this study as a Classroom Action Research in collaboration with an English teacher at the target school. The study was divided into four phases, which included planning, action, observation, and reflection, further categorized into two cycles, namely Cycle I and Cycle II. The study involved a total of 30 eighth-grade students as participants. Data collection methods included pre-assessment and post-assessment scores, questionnaires, and observations. After analyzing and comparing the data between Cycle I and Cycle II, the researcher observed a significant improvement in students' learning interest (reaching over 80%) and their academic achievement (reaching 66.66%) due to the use of interactive learning media. Additionally, there was a notable increase in student engagement during the learning process (exceeding 36.66%) in Cycle II. Consequently, it can be concluded that interactive learning media can effectively address the issue of students' learning interest, as a common challenge faced by teachers. Keywords: Interactive learning media, Learning Interest, English Learning